Anthelmintic efficacy of Gliricidia Sepium, Calliandra Calothyrsus and Artocarpus Heterophyllus by In Vitro Measurement Against Haemanchus contortus Worm - Kustantinah, Kustantinah; Setyono, W.; Dono, Nanung Danar; Orskov, E. R. (Indonesian Society of Animal Science in collaboration with Indonesian Ministry of Agriculture and Faculty of Animal Science UGM, 2014)
This study was conducted to determine the efficacy of some herbaceous forages that contain tannin as anthelmintic for sheep against Haemonchus contortus worm. The forages used were Gliricidia sepium, Calliandra calothyrsus, and Artocarpus heterophyllus. In current study, female Haemonchus contortus worms were isolated from sheep abomasum. In vitro study was done using immersion technique with the concentrations of forage infussion of 0, 10, 30, and 50% (w/v) in a 4x4 factorial arrangement. A screening method was performed afterwards to wxamine anthelmintic capacity of the tested forages by calculating the number of paralyzed or dead worms were done in room temperature every 15 minutes in the first hour and continued subsequently every hour in the next 5 hours. Paralysed worms were determined as from weak worms to completely unmoved ones. Results of current study indicated that increase in lenght of immersion time and concentration of forage infusion increased (P<0.05) the number of paralysed or dead worms. Infusion of Calliandra calothyrsus and Artocarpus heterophyllus showed higher (P<0.05) efficacy when compared to those of Gliricidia. Started at concentration 30%, Calliandra and Artocarpus affect mortality of the worms. Artocarpus heterophyllus showed the higher mortality effect when compared to others leaves (P<0.05). This could be attributed to the tannin content of Artocarpus leaves, which is 2,49% (DM), compared to Calliandra calothyrsus (1.20%; DM) and Gliricidia sepium (0.60%; DM). It can be concluded that, by in vitro evaluation, Artocarpus, Gliricidia, and Calliandra showed anthelmintic (antiparasitic) properties against Haemanchus contortus worms.